1992
DOI: 10.1051/rnd:19920209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary lysine on muscle protein turnover in growing chickens

Abstract: Summary ― Day-old male chickens were fed ad libitum isoenergetic diets containing 20% crude protein but differing in their lysine content (from 6.5 up to 11.3 g/kg). At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 8 publications
8
20
0
1
Order By: Relevance
“…Other researchers, such as Sibbald & Wolynetz (1986), Tesseraud et al (1992), Holsheimer & Ruensink (1993), Scheuermann et al (1995), Edwards et al (1999), Eits et al (2002), and Ajinomoto (2009) observed that increasing lysine levels Kubena et al (1972), Summers & Leeson (1985), Summers et al (1992), Conhalato (1998), and Eits et al (2002) also did not observe any reduction in fat deposition when feeding broilers with increasing lysine levels during the starter phase, which is consistent with our results. On the other hand, Gous & Morris (1985), Holsheimer & Ruensink (1993), Scheuermann et al (1995), Hurwitz et al (1998), and Ajinomoto (2009) concluded that increasing lysine levels during this phase reduced body fat deposition in broilers.…”
Section: Protein and Fat Depositionsupporting
confidence: 92%
“…Other researchers, such as Sibbald & Wolynetz (1986), Tesseraud et al (1992), Holsheimer & Ruensink (1993), Scheuermann et al (1995), Edwards et al (1999), Eits et al (2002), and Ajinomoto (2009) observed that increasing lysine levels Kubena et al (1972), Summers & Leeson (1985), Summers et al (1992), Conhalato (1998), and Eits et al (2002) also did not observe any reduction in fat deposition when feeding broilers with increasing lysine levels during the starter phase, which is consistent with our results. On the other hand, Gous & Morris (1985), Holsheimer & Ruensink (1993), Scheuermann et al (1995), Hurwitz et al (1998), and Ajinomoto (2009) concluded that increasing lysine levels during this phase reduced body fat deposition in broilers.…”
Section: Protein and Fat Depositionsupporting
confidence: 92%
“…Lysine supplementation to a lysine-deficient diet otherwise balanced in terms of other amino acids significantly increased the amounts of protein synthesised and degraded in chicken skeletal muscle (Tesseraud et al, 1992(Tesseraud et al, , 1996a(Tesseraud et al, , 1996b(Tesseraud et al, and 2001. Similar results have been demonstrated Nutrients for production and product quality in the growing pig (Salter et al, 1990) and in humans (Conway et al, 1980;Meredith et al, 1986).…”
Section: Muscle and Adipose Tissue Metabolismsupporting
confidence: 67%
“…Protein fractional synthesis rates (FSR) were measured in vivo according to the flooding-dose method (Garlick et al 1980 and. This method, previously validated in chickens by Muramatsu and Okumura (1985), has been adapted in our laboratory (Tesseraud et al 1992). At 20 min before slaughter, birds that had not eaten for 4 to 6 h received a single intravenous injection (0.8 mL/100 g body weight) of a radioactivephenylalanine solution (150 mmol/L; 1.67-1.85 kBq/L).…”
Section: Methodsmentioning
confidence: 99%